Implementasi Kebijakan Harm Reduction untuk Meningkatkan Moral Knowing tentang Narkotika pada Siswa SMA di Kabupaten Labuhanbatu Utara, Sumatera Utara - Indra Kumalasari; Ika Chastanti; Muhammad Yusuf Siregar (Jurnal Pengabdian Pada Masyarakat, 2020)
HARM REDUCTION POLICY IMPLEMENTATION TO IMPROVE MORAL KNOWING ABOUT NARCOTICS IN HIGH SCHOOL STUDENTS IN REGENCY OF LABUHANBATU UTARA, NORTH SUMATRA. Narcotics are drugs or substances that are usually used for health purposes. Self-destructive behavior that often occurs at this time is the use of narcotics among students due to the low Moral Knowing students about narcotics. This community service aims to improve students' Moral Knowing about narcotics by implementing the Harm Reduction policy by using Cognitive Behavior Therapy counseling and Peer Educators by applying Brainstorming. This community service was carried out at SMA Negeri 1 Kualuh Hulu and SMA Negeri Kualuh Selatan, Labuhanbatu Utara Regency. The results showed a change in behavior in students who became abusers of cannabis type narcotics who were given CBT counseling and there was an increase in students' knowledge about narcotics applied by Peer Educators.